2019
DOI: 10.1002/hed.25477
|View full text |Cite
|
Sign up to set email alerts
|

MVA E2 therapeutic vaccine for marked reduction in likelihood of recurrence of respiratory papillomatosis

Abstract: Background Recurrent respiratory papillomatosis (RRP) or laryngeal papillomatosis is a disease caused by papillomavirus infection. Methods In this phase I/II clinical trial, we evaluated the efficacy of the modified vaccinia Ankara (MVA) E2 virus in the treatment of RRP. Twenty‐nine patients (18 female and 11 male) underwent injection of MVA E2 directly into the borders of the vocal cords where lesions were seen and were monitored by direct laryngoscopy. The immune response was assessed by the determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Clearance of an existing intracellular infection such as HPV is unlikely to occur with preventative vaccination which induces a primarily humoral immune response 11 . Previous studies have demonstrated the clinical benefit of therapeutic vaccines for lrHPV disease using the MMR vaccine 6 and modified vaccinia Ankara encoding bovine papillomavirus E2 5 . It is unclear whether the observed efficacy of these vaccines was due to nonspecific, type I interferon mediated activation of innate immunity given that both of these treatments were administered into lesions directly, and because neither study demonstrated the induction of a specific T-lymphocyte response against lrHPV antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearance of an existing intracellular infection such as HPV is unlikely to occur with preventative vaccination which induces a primarily humoral immune response 11 . Previous studies have demonstrated the clinical benefit of therapeutic vaccines for lrHPV disease using the MMR vaccine 6 and modified vaccinia Ankara encoding bovine papillomavirus E2 5 . It is unclear whether the observed efficacy of these vaccines was due to nonspecific, type I interferon mediated activation of innate immunity given that both of these treatments were administered into lesions directly, and because neither study demonstrated the induction of a specific T-lymphocyte response against lrHPV antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of a lrHPV antigen-specific T-lymphocyte response is likely necessary to clear a chronic lrHPV infection. Although numerous immunotherapies designed to induce HPV16-specific T-lymphocyte immune response have been developed for cancer 2 4 , few such immunotherapies have been developed for lrHPV-driven disorders 5 , 6 . Therapeutic vaccines designed to induce antigen-specific T-lymphocyte responses in the setting of an existing HPV16 infection have demonstrated clinical activity through the induction of HPV-specific T-lymphocyte immunity 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In the latest I/II clinical trial evaluating the possibility of MVA E2 therapeutic vaccines reducing the possibility of recurrence of respiratory papillomatosis (RRP), 13 cases (13/29, 44.8%) of lesions were completely eliminated, and 16 cases (16/29, 55.2%) of lesions recurred 6 to 18 months after treatment. Subsequently, after a second round of MVA E2 therapy, no new recurrence symptoms were observed, indicating that MVA E2 vaccines have a good potential for complete regression of RRP lesions ( Cabo Beltran and Rosales Ledezma, 2019 ). The TG4001 vaccine expresses HPV16 E6/E7, and in a trial evaluating safety and efficacy in patients with (CIN) 2/3, HPV 16 mRNA clearance was associated with CIN 2/3 cytologic and colposcopic regression in 7 of 10 patients ( Brun et al., 2011 ).…”
Section: Research Progress Of Hpv Therapeutic Vaccinesmentioning
confidence: 99%
“…In two trials, one using the measles, mumps and rubella vaccine and the other using a modified vaccinia Ankara vector encoding the bovine papillomavirus E2 gene, intralesional injection of vaccine with or without surgical debulking of disease resulted in significant prolongation of the intersurgery interval or cure of disease in subsets of patients. 77,78 Neither report definitively demonstrated the induction of HPV-specific T cell responses, suggesting that part or all of the clinical benefit induced with these treatments was due to a local, nonspecific, antiviral inflammatory responses involving type I interferon (though such alterations were not studied). More recently, report of clinical benefit in three patients treated with a DNA vaccine encoding HPV 6 E6 and E7 included demonstration of induction of HPV 6-specific T cell responses.…”
Section: Preventative and Therapeutic Hpv Vaccinesmentioning
confidence: 99%